Genetic diversity of forest and savannah chicken ecotypes of Ghana as estimated by microsatellite markers - Osei-Amponsah, R.; Kayang, B.B.; Naazie, A.; Osei, Y.D.; Youssao, I.K.A.; Yapi-Gnaore, V.C.; Tixier-Boichard, M.; Xavier, R. (Animal Science Journal, 2010)
The characterization of indigenous animal genetic resources is a requisite step in providing needed information for the conservation of useful genotypes against future needs. Thus, in this study, 22 microsatellite markers were used to genotype 114 local chickens from the Forest (n = 59) and Savannah (n = 55) eco-zones of Ghana and the results compared to those of the ancestral red junglefowl (n = 15) and two European commercial chicken populations – a broiler (n = 25) and white leghorn (n = 25). A total of 171 alleles were observed, with an average of 7.8 alleles per locus. The local Ghanaian chickens showed higher diversity in terms of the observed number of alleles per locus (6.6) and observed heterozygosity (0.568) compared with the combined control populations (6.0 and 0.458, respectively). However, Wright’s F-statistics revealed negligible genetic differentiation (FST) in local Ghanaian chicken populations. In addition, 65% of the Savannah chickens were inferred to be more likely from the Forest, suggesting a south-north dispersal of chickens from their probable original location in the Forest zone to the Savannah areas. It is concluded that the Forest and Savannah chickens of Ghana are a single, randomly mating unselected population, characterized by high genetic diversity and constitute a valuable resource for conservation and improvement.
Keywords: Characterization; Genetic Diversity; Local Chicken; Microsatellite